Antioxidant activity and cytotoxicity of solubilized C60 and its conjugates with butylated hydroxytoluene - Nunes, A. S. (2011)
It has been described that fullerenes (C60) present interesting properties with potential application in clinical conditions related to oxidative stress. One of the most prominent features of fullerenes is the ability to quench free radicals. However, because of its poor solubility, this has been studied mostly in organic solutions, while the antioxidant activity and cytotoxicity of fullerenes and their derivates in aqueous medium is not well characterized. The antioxidant capacity of synthesised C60-conjugates has been investigated and its was higher comparing to C60 isolated. The aim of this study was to assess the viability of C60-conjugates by determining its antioxidant activity and cytotoxicity in bio-relevant media.